Identification and Analysis of Meat Species Using Laser Induced Breakdown Spectroscopy (LIBS): A Review - Ahmad, Khairunnas; Saiful, Saiful; Nur, Syahrun; Iqhrammullah, Muhammad; Febriani, Febriani (Journal of Carbazon, 2023)
The high price of beef and its processed products has led to many cases of adulteration with pork, resulting in issues related to halal food assurance. Therefore, it is crucial to conduct identification and analysis of the types of meat used in order to maintain food halalness. One of the methods currently advancing in the identification and analysis of meat types is Laser-Induced Breakdown Spectroscopy (LIBS). The aim of this study is to determine the capability of Laser-Induced Breakdown Spectroscopy (LIBS) in identifying and analyzing various types of meat. The study results indicate that the Laser-Induced Breakdown Spectroscopy (LIBS) method is capable of identifying and analyzing meat types with simple sample preparation and accurate outcomes compared to other methods such as Real Time-PCR, Enzyme-Linked Immunosorbent Assay (ELISA), Electronic Nose System, Fourier-transform infrared spectroscopy (FTIR), and Raman spectroscopy. The Laser-Induced Breakdown Spectroscopy (LIBS) method can be combined with various chemometric methods such as PCA, PLS, and MSC. Laser-Induced Breakdown Spectroscopy (LIBS) can identify and analyze various types of meat with an accuracy of up to 100% in shrimp and clams mixed sample. In conclusion, the combination of LIBS and chemometric methods demonstrates promising results in identifying and analyzing meat types.